PERANCANGAN M-FIN VERTICAL SURFACE SEBAGAI ALAT FILTRATION UNTUK MENURUNKAN KOMPOSISI AIR FORMASI PADA LAPANGAN S-07 - Sefilra Andalucia; Aldo Setiawan; Westen Tera Kiranda (Jurnal Cakrawala Ilmiah, 2025)
M-FIN is a filtration device functioning to filter or separate impurities contained in formation water which can cause scale. In addition, using M-FIN which has filter media in form of coal, zeolite, silica sand and pumice it is expected reduce the composition of fornation water in forn of ions which will be formation water which has been tested for filtration. It can be used as injection water that meets specifications. Prior to designing the tool, a test was carried out on formation water in form of filtration using filter media (coal, zeolite, silica sand and pumice) on a lab scale. In this lab test, in addition to filtration, a titration is carried out to read the ion value or the composition of the formation water whether the formation water sample changes in the composition of the formation water before filtration without filter media and after using filter media which aimed to identify whether the formation water was suitable or not used as injection water. The test results for formation water samples before filtering without filter media did not meet the Good Water Injection Requirements specifications, namely the parameters SI, TSS, TDS, NTU (Trbidity), CI, Fe3+, and pH. Therefore, a second filtration was carried out using filter media (coal, zeolite, silica sand, and pumice). From the results of the sarnple test, it indicated a change namely a decrease (sample B) in the SI parameter by 100%, TSS by S6%, TDS decreasing by 69%, NTU decreasing from 56 to a value of 21, for C1- from a value of 4.8 decreased to 3.1 while Fe3+ from 0.018 to 0.011 and the pH decreased to 8.